Performance, carcass and meat characteristics of ½ Flemish breed cattle, finished in annual ryegrass pasture, supplemented with soybean hulls - Favaro, Vanessa Ruiz (2021)
The objective was to evaluate the performance and characteristics of the carcass and meat of beef steers, under annual ryegrass grazing with and without soybean hulls supplementation. Sixteen ½ Flemish bovines, castrated, were distributed in two treatments: 1) control, exclusive feeding on annual ryegrass pasture; 2) supplementation with soybean hulls at 0.6% of live weight. The animals' average age and initial weight were 21 months and 417.5 kg, respectively. The animals were slaughtered when they reached at least 3 mm cover fat thickness (CFT), at 26 months of age. There were no significant effects of treatments for performance and carcass and meat characteristics (P> 0.05). The crossing with the Flemish breed resulted in carcasses weighing over 300 kg. The finishing of cattle in annual ryegrass pasture cv. Winter Star provided carcasses with the quality standards required by refrigerators and consumers with adequate values for CFT, pH, tenderness and color of meat and fat.